Latinx Geographies: Opening Conversations - Cahuas, Madelaine Cristina; Douglass-Jaimes, Guillermo; Faiver-Serna, Cristina; González Mendoza, Yolanda; Martinez-Lugo, Diego; Ramírez, Margaret Marietta (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
With increased interest in Latinx geographies there is a need for more in-depth exploration of how Latinx geographers are approaching this work in their own words. In this article, we open a discussion on Latinx geographies that is grounded in our multiple, different, embodied experiences as Latinx geographers who have gathered over the last several years to have conversations, create spaces and build relationships of care and accountability with each other. We reflect on how we each arrived to Latinx geographies, what it means to us, how we do Latinx geographies and what is on the horizon. We refuse singular or imposed definitions, and collectively imagine an expansive, nuanced, and relational Latinx geographies that critically engages with difference, conquest, power, and liberation across Turtle Island and Abya Yala.